PENGARUH HARGA, VARIASI PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PAKU DI UD. BADARUDIN GROUP TULUNGAGUNG - Saputra, Mohammad Febri Rendra; Munir, Miftahul; Putra, Agung Pambudi Maha (Commodities, Journal of Economic and Business, 2023)
The issues discussed are regarding price, product variety, and service quality to reflect the relationship to customer satisfaction when purchasing nail products at UD. BADARUDIN GROUP TULUNGAGUNG. The purpose of the discussion is to determine the factors of price, product variety, and service quality that affect nail customer satisfaction at UD. BADARUDIN GROUP TULUNGAGUNG. The population and samples taken are consumers or customers of nail products who have made purchases at UD. BADARUDIN GROUP TULUNGAGUNG. The analysis technique used is Validity Test, Reliability Test, Classical Assumptions, Multiple Linear Regression Analysis. The results showed that the price partially did not have a significant effect on nail customer satisfaction. It can be seen from the results of the t test, the value of t price is 0.375 > 0.05. Product variation and service quality partially have a significant effect on nail customer satisfaction, it can be seen from the results of the t test, the t value of product variation is 0.000 <0.05 and the t value of service quality is 0.027 <0.05. Simultaneously price, product variety, and service quality have a significant effect on nail customer satisfaction, it can be seen from the results of the F test, the F value of price, product variety, and service quality is 0.000 <0.05. The value of the determinant coefficient (R2) is 0.630. This can be interpreted that the independent variables (price, product variety, and service quality) can explain the dependent variable (customer satisfaction) of 63.0%, while the rest is explained by other factors not examined such as store image, promotion, location and others.